Situational factors that influence impulse buying behaviour among local and international consumers - Ng, Joe Sheng (2019)
This study was carried out to explore the influence of situational factors on impulse behaviour among local and international consumers situated in Malaysia. The researcher examined four factors that affect impulse buying behaviour. Factors included Store Environment, Store Employees Assistance, Money Availability and Time Availability. Stimulus-Organism-Response Model developed by Mehrabian and Russell (1974) was used to explain the independent variables and dependent variable. This study has adopted quantitative research method and convenience sampling method. The target population are local and international consumers situated in Malaysia. Primary data was collected through the distribution of 160 copies of self-administered questionnaires and it was then being analysed using SPSS. The questions and scales in the questionnaire were considered to be reliable as all Cronbach’s Alpha value are above 0.7. Data analysis methods that were being performed in this research include descriptive analysis, reliability test, multiple regression analysis and independent T-test. Based on the results of multiple regression analysis, it indicated that both Store Environment and Time Availability have significant relationship with impulse buying behaviour while there is no significant relationship between Store Employees Assistance and Money Availability towards impulse buying behaviour. Also, according to the results of independent T-Test, it showed that there is no significant difference in impulse buying behaviour among Malaysian and Non-Malaysian.